A REALITY IN A DEVELOPING COUNTRY- BENIN: DIAGNOSIS OF CANCER WITH THE ACTIVATION OF AUTOMATED IMMUNOHISTOCHEMISTRY - Zanin, Tiziano (LIFE: International Journal of Health and Life-Sciences, 2019)
Background: In the Benin-West state of Africa, cancer is one of the most frequent causes of death. For this reason from September 2015 at Saint John of God Hospital in Tanguieta – Benin – a Histopathology Laboratoy is active with the aim to make diagnosis and address towards adequate therapeutic programs patients affected from cancer and other diseases. The Laboratory has been equipped with a tele pathology system (Cross SS, Dennis T, Start RD. 2002 and Della Mea V. & Beltrami CA. 2000) and from 2018 with an Automatic System for Immunochemistry.Objectives, methods and outcomes: In the last 20 years, in collaboration with the association APOF (Pathologists across the border), diagnostic laboratories have been developed in various African countries: Tanzania - Uganda - Djibouti, etc. Immunohistochemistry has been introduced in these laboratories to formulate a correct and complete diagnosis.In Benin we had a technological breakthrough by introducing an automated immunohistochemistry system. The funds were obtained from the FAI (International Assistance Foundation) of Lugano (Switzerland) and from the UTA – Onlus.The use of validated protocols, the contribution of international experts through telepathology, the training of technical personnel on site, allowed the formulation of correct diagnoses.Conclusion: The development of complete histopathological diagnostic services of automated ICHs, such as that of Benin, is of fundamental importance for the fight against cancer in developing countries. Cancer is fought with research but also with a correct diagnosis.